Community-Driven Collaborative Governance for Sea Turtle Conservation in Coastal Tourism Areas - Khusnul Prasetyo; Dadar Pusparini; Lutfi Amanah; Naila Khotfatul Janah; Nur Anis Amalina Binti Amir Hamzah (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
Sea turtle conservation in coastal tourism areas depends not only on ecological knowledge but also on the ability of different actors to work together. This study examines community-driven collaborative governance in sea turtle conservation at Kembar Terpadu Beach, Kebumen Regency. It employed a qualitative single-case study design. Data were collected through in-depth interviews with four informants representing site management, the media team, a local resident who also operates a micro, small, and medium enterprise, and the Kebumen Regency Tourism and Culture Office. Interviews were complemented by field observation and document analysis. The findings show that collaboration emerged from community leadership and concern over turtle-egg collection and the hunting of nesting females. This initiative generated local commitment, an internal division of responsibilities, and networks with government agencies and external partners. However, the collaboration continues to rely heavily on personal relationships and has not been fully supported by stable cross-organizational roles, funding, performance data, and leadership succession. The study demonstrates that community strength provides the foundation for collaboration, while its long-term sustainability depends on transforming local initiatives into shared institutional arrangements.